Bridging Gaps: Transformative Applications of Medical Communication in Healthcare Insurance - Mitesh Mohan Hood; Shaloo Varma (New Advances in Business, Management and Economics Vol. 1, 2025)
Medical communication plays a significant role in the healthcare insurance industry, serving as a critical tool for accurate claims processing, patient education, and regulatory compliance. By translating complex medical information into clear and actionable formats, medical writers enhance transparency, reduce the risk of fraud, support efficient decision-making processes and enhance collaboration in healthcare communication. Emerging technologies such as digital health platforms, artificial intelligence (AI), and big data analytics are driving transformative changes in the industry. These innovations improve the precision and accessibility of medical documentation, while also enabling predictive analytics and more robust risk assessment models. Through structured communication, medical writers play a pivotal role in bridging gaps between healthcare providers, insurers, and patients, fostering trust and improving operational workflows. This study explores the diverse applications of medical writing within the insurance sector, emphasizing its critical role in addressing industry complexities, exploring future trends in medical writing and communication, and driving progress toward a more transparent, patient-focused, and technology-driven insurance ecosystem.